Addressing the Problem of Severe Underinvestment in Mental Health and Well-Being from a Human Rights Perspective - Faraaz Mahomed (Harvard FXB Center for Health and Human Rights, 2020)
Throughout the world, mental health remains a neglected priority, low on the agenda of policy makers and funders at the national and international levels. While this is shifting somewhat, there remains a considerable need to address the underprioritization of mental health and well-being, perhaps even more so in the wake of the COVID-19 pandemic. However, given the history of mental health interventions-which have overemphasized the biomedical model and have thus resulted in coercion, denial of life in the community, and unnecessary pathologization of human experience-there is also a need to ensure that increased funding does not simply replicate these mistakes. This is particularly true in the current landscape, where efforts to "scale up" mental health and to reduce "treatment gaps" are gaining momentum and where post-pandemic responses are still being formulated. As the potential for global mechanisms for funding mental health increases, national and international funders should look to practices that are rights affirming and contextually relevant. In this paper, I explore the current landscape of mental health financing, in terms of both national resource allocation and development assistance. I then outline the momentum in global mental health that is likely to materialize through increased funding, before considering ways in which that funding might be utilized in a manner that promotes human rights.